Implementing The Confiscation Of Confiscated Objects For Criminal Acts Of Corruption That Have Impaired Value - Agung Abadi (Faculty of Law, Universitas Lampung, 2022)
This research discuss the implementation of confiscating criminal acts of corruption that have decreased in value. The author raised this matter because, based on data released by Indonesia Corruption Watch (ICW), there were 533 (five hundred and thirty-three) cases throughout 2021. Based on this data, it was found that the total potential state losses incurred reached Rp 29.4 trillion. In contrast to the magnitude of the losses incurred, on the other hand, based on the results recorded by the Corruption Eradication Commission (KPK) that the return of state losses was only Rp 2.6 trillion, which consisted of payment of fines, compensation for the spoils, and Rp 3 billion in the form of payment of status determination and use of grant funds. From the existing problems, the author examines how to manage the confiscated objects of corruption so as not to experience a decrease in value. This research uses a normative juridical writing method; namely, the law is conceptualized as what is written in legislation, or the law is seen as a gift or norm, which is a benchmark for human behavior considered appropriate and supported by data found on the internet. After researching the problems discussed in this journal, this can be overcome by holding an auction in advance of confiscated objects that will experience a decline in value so that the recovery of state financial losses can take place optimally, which needs to be also supported by a good work ethic from law enforcement officials. The law, namely by taking good care of confiscated objects so that they do not experience a decline in value and integrated data collection in order for the confiscated objects to remain safe and unrewded or not recorded.